Higher Education in the Far East: Market Position and Development Needs of the Region - T. N. Blinova; A. V. Fedotov (Высшее образование в России)
The article analyzes the compliance of the structure of supply and demand for higher education services with the staffing needs for the development of the Far Eastern Federal District. The authors dwell on the main market factors affecting the demand for higher education (the number of potential consumers, monetary incomes of the population, employment opportunities after graduation, the level of possible wages in the specialty received, the price of secondary vocational education, the needs of economics for specialists with higher education by groups of training areas), their influence on the market for higher education services in the macroregion. In the context of enlarged groups of specialties and areas of training, an assessment of the demand and supply of higher education services and their compliance with the development needs of the macroregion and its constituent entities is given. The article shows that the system of forming management decisions in terms of harmonizing the demand for higher education services, their supply and development needs of the region requires a deeper differentiation in conjunction with factors affecting the market for higher education services. The main directions of improving the system of forming management decisions by redistributing powers between higher education authorities towards the expansion of regional and macroregional authorities are proposed.